To understand the characteristics of stable isotopes and trace elements in groundwater of Thirumanimuttar sub-basin, Tamil Nadu, India - Vasanthavigar, M.; Srinivasamoorthy, K.; Prasanna, Mohan; Poovalinga Ganesh, B. (NORTH UNIV BAIA MARE, FACULTY MINERAL RESOURCES & ENVIRONMENT, DR VICTOR BABES 62-A,, BAIA MARE, 430083, ROMANIA, 2012)
Thirumanimuttar River is the only ephemeral stream passing through the heart of the Salemcity and flows towards southwest and joins river Cauvery in the southern region of Kuduthurai at near Paramathi Vellur forms the spinal cord for urban development. A number of industrial units including dyeing/bleaching and sago industries were located within the core zone. The industrial effluent and sewage water disposal by conversion of natural streams and water bodies as sewer drains. An attempt has been made to study the characteristics of stable isotopes and trace elements in groundwater of Thirumanimuttar sub-basin. Hence, thirty-four groundwater samples were collected for stable isotope [Oxygen (18O), Hydrogen (2H or Deuterium)] and trace element studies. The study reveals that the groundwater samples undergone some evaporation prior to infiltration. The d-excess of the groundwater were varied between -4.89 to 10.08 ‰ indicating that the water undergone strong evaporation during recharge into the local groundwater system. The trace element study indicates that some trace metals such as Al, Ni and Pb exceeds the acceptable limit. The spatial distribution map shows higher concentration of Cr is increased from north to south due to the textile dyeing units were located around in the region.